1988
DOI: 10.1055/s-2007-1025046
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Threshold, Anaerobic Threshold, and Maximal Oxygen Uptake of Japanese Speed-Skaters*

Abstract: The purpose of this study was to investigate the physiologic and metabolic parameters of speed-skaters with different training regimes and performance level and examine some physiologic prerequisites for speed-skating. The subjects were 25 male speed-skaters including members of the 1984 Japanese National Speed Skating Team whose ages ranged from 19 to 25 years. Aerobic threshold (AerT), anaerobic threshold (AnT), and VO2max were determined during a progressive bicycle ergometer exercise. The power was increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Evidence for this statement might be deduced from a comparison of the mean test results with corresponding values reported for elite senior skaters. With respect to I702 .... the junior skaters appear to have fallen completely within the range of values found for senior skaters (Ingen Schenau et al 1983;Ingen Schenau and de Groot 1983a;Foster et al 1990) and were higher than those found for Japanese senior skaters (Nemoto et al 1988). For the sprint test we have found comparable values in senior male skaters (unpublished results) while the values of our junior men and women were significantly greater than those reported for American skaters (Foster et al 1990).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Evidence for this statement might be deduced from a comparison of the mean test results with corresponding values reported for elite senior skaters. With respect to I702 .... the junior skaters appear to have fallen completely within the range of values found for senior skaters (Ingen Schenau et al 1983;Ingen Schenau and de Groot 1983a;Foster et al 1990) and were higher than those found for Japanese senior skaters (Nemoto et al 1988). For the sprint test we have found comparable values in senior male skaters (unpublished results) while the values of our junior men and women were significantly greater than those reported for American skaters (Foster et al 1990).…”
Section: Discussionsupporting
confidence: 51%
“…kg-1. min -1 for the men and 50-60 ml.kg -1 -min -1 for the women (Ekblom et al 1967;Maksud et al 1970;Ingen Schenau et al 1983Nemoto et al 1988;Foster et al 1990). Their anaerobic power output as measured during 30-s supramaximal cycling has belonged to the highest recorded by any group of athletes (up to mean power outputs of 14 W.kg -1 for men and 12 W.kg -1 for women; Ingen Schenau et al 1988;Foster et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported, as an index of the element of physical strength, that a significant correlation has been found between the maximum anaerobic ability and muscular strength for knee extension and competitive results in short distance events [1][2][3] . It has also been reported that there is a significant correlation between the maximum oxygen intake, which is the index of the maximum aerobic ability, and competitive results in long distance events 4) . In addition, when it comes to specific physical strength training methods, the fact that high altitude training and low oxygen training [5][6][7] are effective at not only improving aerobic ability but also anaerobic ability, has attracted attention.…”
Section: Introductionmentioning
confidence: 95%
“…van Ingen Schenau et al (1990) have shown that a fast acceleration (high initial power output) is crucial for the sprinting events (500 and 1000 m), while for the long distances the skaters should combine a fast but short‐lasting start with a constant power output following the start in order to minimize air frictional losses. The list of determinants of success in speed skating also includes the following factors: increased cross‐sectional area of quadriceps femoris muscles (Kanehisa et al 1996); optimal pacing strategy (Muehlbauer et al 2010; Hettinga et al 2011); anthropometric features (shorter legs and longer trunks; Sovak & Hawes, 1987); and increased aerobic capacity (Nemoto et al 1988).…”
mentioning
confidence: 99%